Sociological analysis of preparedness of pass of Ukraine institutions to reorganization changes in the project mechanism realization: «Transition for payment of contracts with national health service of Ukraine» - Rosha, L. G. (Journal of Education, Health and Sport, 2019)
The goal is to study the assessment of the doctors working in the PAS regarding the readiness of the PAS institutions ofUkraineto implement the project mechanism: "The transition to paying for contracts with the National Health Service of Ukraine" within the further development of decentralized organizational transformations of the administrative system of the PAS ofUkraine. Materials and methods. 53 doctors (PAS staff ofUkraine) were interviewed by a specially designed questionnaire. Statistical processing of the obtained results is carried out using generally accepted statistical methods. Results. The comprehensive assessments of the readiness of PAS institutions inUkraine to implement the project mechanism: "Going to pay for contracts with the National Health Service of Ukraine", taking into account the basic principles of further reorganization transformations of structural management, based on the implementation of the model of the project of the regional pathoanatomical center (SRC). Conclusions. The results of the study showed that, according to surveyed doctors, the current system of PAS of Ukraine within the framework of the implementation of the mechanism of decentralized organizational reform by 2020 will be ready only by 67.5% for the implementation of the project mechanism, similar results are associated with existing problems in the field of financing of PAS establishments in Ukraine and the urgent need to develop new investment mechanisms aimed at realizing the search for the necessary financing of the project’s economic and resource support.